Имя твое: роман / Петр Проскурин - Проскурин Петр Лукич (Современник, 1993)
Экземпляры: ф30 (20200228) / Инвентарный номер: 59097 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: П 82 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6